Mediating Local Wisdom through Students’ English Culinary Tutorials for Global Audiences - Utami, Setyo (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study investigates how Indonesian university students mediate local wisdom and promote tolerance through English-language culinary tutorials on YouTube. Using multimodal discourse analysis and thematic analysis, the research examined five student-produced videos and reflective notes from thirteen participants. The findings reveal that students employed linguistic, visual, and paralinguistic strategies to communicate both procedural clarity and cultural meaning. They integrated religious and moral values, showcased regional diversity, and used English as a medium of intercultural storytelling. Through reflective engagement, learners demonstrated growth in intercultural communicative competence (ICC), including openness, empathy, and moral awareness. The study concludes that digital project-based learning enables students to act as cultural mediators—bridging local heritage with global audiences—while redefining English as an inclusive and ethical communicative tool rooted in Indonesian cultural identity.